HUBUNGAN KONSEP DIRI DAN KONFORMITAS TERHADAP KELOMPOK TEMAN SEBAYA DENGAN PERILAKU MEROKOK PADA REMAJA SEKOLAH MENENGAH PERTAMA (SMP) - , Sulartiningsih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was done to investigate whether there is any correlation between self concept and conformity toward peer groups and smoking behavior and to analyze whether there is any effective contribution of self concept and conformity toward peer groups and smoking behavior in adolescents in Junior High School. The subjects of the research were 111 students of junior high school age 12 â 16 years old, smokers, Junior High School students in the area of Depok Sub-district Sleman District. Data collecting method used self concept scale, conformity scale toward peer groups, and smoking activity scale. Research data were analyzed by using double regression analysis. The result of research showed that there was significant negative correlation between self concept and smoking activity -0.557